2009
DOI: 10.12660/bre.v29n22009.3439
|View full text |Cite
|
Sign up to set email alerts
|

Political Economy and Tenure of Coaches in Brazilian Soccer

Abstract: In this paper we built a model of political economy to explain the tenure of coaches in Brazilian soccer. According to the model, a club's board of directors maximizes its reputation by choosing the grade of the technical committee. Then, based on data from the Brazilian National Soccer League, we used coaching continuity as a proxy for the grade variable and duration analysis techniques to test the model's propositions. According to the empirical analysis, and in line with the theoretical model, a coach's per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…Such a stressful environment has been confirmed by Olympic coaches in the United States [25] and in Great Britain [40], as they appraised how successful coaching performance is essentially linked to strategic planning and support networks. Moreover, Rocha et al [41] highlighted the political background influencing coaching tenure in the Brazilian football league, whereby club directors minimize the effects of poor performance on their board's reputation by reducing their trust in head coaches. In Germany, Orlowski et al [42] and Wicker et al [43] identified that working conditions, income, and job stability can be decisive aspects to increase coaching retention and minimize labor migration at the elite level, thus decreasing the occurrences of employment termination.…”
Section: Termination Of Employmentmentioning
confidence: 99%
“…Such a stressful environment has been confirmed by Olympic coaches in the United States [25] and in Great Britain [40], as they appraised how successful coaching performance is essentially linked to strategic planning and support networks. Moreover, Rocha et al [41] highlighted the political background influencing coaching tenure in the Brazilian football league, whereby club directors minimize the effects of poor performance on their board's reputation by reducing their trust in head coaches. In Germany, Orlowski et al [42] and Wicker et al [43] identified that working conditions, income, and job stability can be decisive aspects to increase coaching retention and minimize labor migration at the elite level, thus decreasing the occurrences of employment termination.…”
Section: Termination Of Employmentmentioning
confidence: 99%
“…Já em relação a estudos que utilizam o futebol brasileiro, pouco, relativamente, foi produzido até o momento na temática de economia do esporte diante da relevância do Brasil no cenário do futebol mundial. Ainda assim, é possível destacar alguns trabalhos seminais, como é o caso do estudo desenvolvido por Giovannetti et al (2006), Rocha et al (2009). O primeiro estudo mede a fidelidade das torcidas brasileiras.…”
Section: Revisão Da Literaturaunclassified
“…Assim, se o papel desenvolvido por técnicos de futebol é preponderante ou não negligenciável para o êxito esportivo, conforme afirmam Anderson & Sally (2013), é de se esperar a troca em caso de resultados negativos sucessivos, objetivando um melhor desempenho (Rocha et al 2009). Nesse caso, os diretores envolvidos no processo de decisão comparam o desempenho real às expectativas.…”
Section: Introductionunclassified